A Chemical Vapor Deposition Diamond Reactor for Controlled Thin‐Film Growth with Sharp Layer Interfaces. Issue 4 (21st February 2023) - Schätzle, Philip; Reinke, Philipp; Herrling, David; Götze, Arne; Lindner, Lukas; Jeske, Jan; Kirste, Lutz; Knittel, Peter
Abstract : Diamond Thin‐Film Growth In article 2200351, Philip Schätzle and colleagues present a chemical vapor deposition diamond reactor with sample transfer equipment. This enables a rapid removal of the sample from plasma, interrupting the growth process immediately. Growth resumption can then be performed when re‐introducing the sample into changed plasma compositions. This allows for sharp doping profiles in diamond thin films as required by diamond quantum technologies.